2007
DOI: 10.1186/1471-2105-8-350
|View full text |Cite
|
Sign up to set email alerts
|

Selection of long oligonucleotides for gene expression microarrays using weighted rank-sum strategy

Abstract: BackgroundThe design of long oligonucleotides for spotted DNA microarrays requires detailed attention to ensure their optimal performance in the hybridization process. The main challenge is to select an optimal oligonucleotide element that represents each genetic locus/gene in the genome and is unique, devoid of internal structures and repetitive sequences and its Tm is uniform with all other elements on the microarray. Currently, all of the publicly available programs for DNA long oligonucleotide microarray s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 35 publications
0
75
0
Order By: Relevance
“…These synchronous, monoclonal, erythrocytic isolates were cultured ex vivo from the early ring stage to the schizont stage (see Table S1) (12,14). Transcriptional analysis using a genome-wide long oligonucleotide microarray designed by the recently established algorithm OligoRankPick (15) showed that during the P. vivax IDC, each gene is activated at a particular developmental stage analogous to P. falciparum ( Fig. 1) (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These synchronous, monoclonal, erythrocytic isolates were cultured ex vivo from the early ring stage to the schizont stage (see Table S1) (12,14). Transcriptional analysis using a genome-wide long oligonucleotide microarray designed by the recently established algorithm OligoRankPick (15) showed that during the P. vivax IDC, each gene is activated at a particular developmental stage analogous to P. falciparum ( Fig. 1) (6).…”
Section: Resultsmentioning
confidence: 99%
“…From these, 5,063 are represented by a single oligonucleotide, whereas 272 genes (typically long ORFs) are represented by two or more oligonucleotide elements. The P. vivax microarray oligonucleotide set was designed by OligoRankPick (15). Sequences of all oligonucleotides and further information are available online at http:// zblab.sbs.ntu.edu.sg/vivax/index.html.…”
Section: Methodsmentioning
confidence: 99%
“…The five parasite lines were tightly synchronized to a 0-to 5-h window, and RNA was obtained at seven time points along the asexual blood cycle. Relative transcript levels were determined by hybridizing samples against a common reference pool in a long-oligonucleotides microarray (Hu et al 2007). Principal component analysis (PCA) revealed clustering of samples collected at the same time point, as expected for wellsynchronized samples.…”
Section: Identification Of Genes Under Clonally Variant Expressionmentioning
confidence: 99%
“…The microarray used in this study is based on long oligonucleotides (70 nt) designed against the PlasmoDB 4.4 release of the 3D7 reference P. falciparum genome (Hu et al 2007). We reannotated the microarray against the 3D7 PlasmoDB 7.0 genome release, which resulted in changes in more than 700 probes, including removal of cross-reactive probes.…”
Section: Microarray Experimentsmentioning
confidence: 99%
“…Numerous publications and software tools are currently available for designing DNA microarray probes (8)(9)(10)(11). However there are no software packages or even design rules published so far specifically for DNA barcode probes.…”
mentioning
confidence: 99%